Evaluating Factors Influencing Quality Assurance of Building Construction Projects: A PLS-path Modelling Approach - Njoki Gacheru, Esther; Diangá, Stephen; Masu, Sylvester; Onchiri, Richard (Multidisciplinary Journal of Technical University of Mombasa, 2023)
The quality of building construction projects in Kenya has been a challenge throughout recent years. Despite the presence of regulatory agencies, buildings have continued to portray a significant lack of quality with several buildings collapsing in major towns. The purpose of this study was to evaluate factors influencing quality assurance of building projects as well as to determine the magnitude of the influence. Eight indicators of quality assurance were identified from ISO 9001 elements of quality assurance. Similarly, eleven factors influencing quality assurance with five indicators each were identified from literature.  A questionnaire survey of building contractors was carried out to evaluate factors influencing quality assurance of building construction projects. The findings of the survey were analysed using SPSS and SmartPLS to determine which studied factors were most critical. Findings indicated the most critical factors as; contractor related factors, consultant related factors, inspection and supervision related factors, communication related factors, and quality standards and measurements related factors. The least ranked factors were equipment related, and health and safety related factors. All eleven factors were however found to have significant influence on quality assurance of building construction projects. The findings of this study are important in highlighting critical areas in which contractors should channel resources to enhance quality assurance of building projects.